MANAGEMENT OF BLEEDING IN A PATIENT WITH ACQUIRED HAEMOPHILIA A: A CASE REPORT - Mihriban Yıldırım; Muzaffer Keklik; Şerife Emre Ünsal; Nesibe Taşer Kanat; Hacı Ahmet Aslaner; Gülşah Akyol; Neslihan Mandacı Şanlı; Ali Ünal (Hematology, Transfusion and Cell Therapy)
Objective: Acquired haemophilia A (AHA) is a blood clotting disorder caused by the presence of autoantibodies that interfere with the function of factor VIII, often called factor VIII inhibitor (1). It has a prevalence of about one per million per year. Acquired haemophilia A is usually associated with autoimmune diseases, malignancies, skin disorders, drug interactions, and the postpartum period, and as many as 50% of cases have unknown causes (2). Bleeding often occurs under the skin (purpura/ecchymosis) and in soft tissues, and rarely in the joints (haemarthroses) (3). The presence of Factor VIII inhibitors causes a disruption in the intrinsic coagulation pathway, leading to prolongation of the activated partial thromboplastin time (APTT) parameter, which does not improve after mixing test, and has low Factor VIII activity (2). The management of patients with AHA aims to control bleeding and its complications and to eradicate factor VIII inhibitors. Immunosuppressive agents are usually used to eradicate factor inhibitors.In this study, we report a case of acquired haemophilia A presenting with spontaneous unprovoked bruising and discuss the approach to diagnosis and how to alert the clinician to suspect this potentially rare but devastating disease. Case report: A 67-year-old man presented to the emergency department with bruising on his left hand and right leg for approximately 10 days. The patient had no history of trauma.He had a history of hypertension and chronic obstructive pulmonary disease. Approximately 2 months prior to presentation, he had complained of bruising on his arms after taking medication (etodolac, ampicillin-sulbactam) (Figure 1). There had been no bleeding after the cholecystectomy.Physical examination revealed an anteroposterior diffuse haematoma extending from the right inguinal to the popliteal area and a haematoma on the dorsal aspect of the left hand (Figure 2). Other systemic examinations were normal.All laboratory results showed the initial complete blood count; normochromic anaemia, normal platelet count and prolonged activated partial thromboplastin time (APTT) with normal prothrombin time (PT). Liver and renal function tests were within normal limits. The test results showed very low factor VIII activity with normal von Willlebrand factor and fibrinogen levels (factor VIII activity: <0.4%). There was no improvement in the mixing test. The factor VIII inhibitor level was 96 Bethesda Units (BU). Workup for connective tissue disease and malignancy screening were otherwise negative.The patient's USG showed a 21 × 20 × 65 mm haematoma in the muscle planes of the right thigh, which was drained by interventional radiology.The patient was then admitted to the haematology clinic and started on methylprednisolone at 1 mg/kg/day. However, recombinant factor VIIa followed by activated prothrombin complex concentrate was administered to the patient whose bleeding could not be controlled. In addition, the patient whose bleeding could not be controlled received three sessions of plasmapheresis every other day.After three weeks of steroid treatment, cyclophosphamide was added due to lack of response and treatment was continued for approximately 5 weeks.Factor 8 activity returned to normal after approximately two months and no inhibitor was detected after this period. Conclusion: Acquired haemophilia A (AHA) is a rare condition in which the body produces autoantibodies against factor VIII (1). Approximately half of cases are associated with a disease, and the others are idiopathic. The most commonly reported associations are autoimmune diseases, solid organ and lymphoproliferative malignancies, skin disorders, medications and pregnancy (2).Patients usually present with subcutaneous and mucocutaneous bleeding, followed by muscular, gastrointestinal, genitourinary and retroperitoneal bleeding (4). Our patient above presented with both subcutaneous and intramuscular haematomas.The first suspicion of this condition is usually based on a coagulation profile. This may show an isolated prolonged APTT ratio in a patient with unexplained bleeding. The platelet count will usually be normal. An isolated prolonged apTT raises two possibilities; either an absolute deficiency of intrinsic pathway coagulation factors, or the presence of antibodies or inhibitors to these factors (5). The BU test is performed to quantify the inhibitor titer and confirm the diagnosis. The stronger the inhibitor, the higher the BU (6). In general, a titer greater than 5 BU indicates a high titer inhibitor. Our patient had a reported inhibitor titer of 96 BU.Bypassing agents such as active recombinant factor VII have shown good results in stopping bleeding, while immunosuppressive drugs such as corticosteroids, cytotoxic agents (cyclophosphamide, cyclosporine) and rituximab (anti-CD-20 monoclonal antibody) are often used to eradicate inhibitors (7).Our patient, who presented with diffuse bleeding in the right leg and left hand, was also difficult to treat due to high factor inhibitor level and was hospitalised for approximately one month.In conclusion, AHA should be recognised and treated rapidly, as delays in diagnosis can have serious consequences. In our patient, AHA was diagnosed rapidly and treatment and bleeding control were effective.